Communication Features of a Qualified Doctor with Different Patients (Journal of Pedagogical Inventions and Practices, 2023)
This article is aimed at improving the speech culture of future doctors, it includes information about the characteristics of communication with different patients, historical models of communicative speech, types of patients depending on their mental state, and human temperament. In addition, the article highlights the practical aspects and necessity of communicating with patients suffering from various diseases and their relatives.